Images Of 'loneliness In Edgar Allan Poe's Poems: A Semiotic Study. - Mega, Afaf (جامعة الوادي - University of Eloued, 2020)
We endeavor through our researh paper to expose the importance of the semiotic theory in the analysis of poetry in particular. The idiosyncrasy of poetry makes it the most challenging genre to be analysed in order to get the right and intended meaning of the poet. For this reason, we suggest that we have to invest in the semiotic field for the interpretation of poetry because we see that it provides the interpreter with a variety of tools and concepts that help in going deeper in the analysis of poetry. However, we have noticed that poetry is the least genre which benefitted from semiotics inspite of the seminal works of Michael Riffaterre in this field. Therefore, we would like to elaborate in this field and demonstrate the rewarding outcomes of the semiotic analysis of poetry. In order to achieve our objectif, we depicted a collection of poems that were written by the American poet Edgar Allan Poe and analysed the different images and functions of the concept of ‘loneliness’ on the light of the concepts of the semiotician Umberto Eco. In the end, we found out how the results are satisfactory in revealing the artistic strategies of Poe in employing the theme of loneliness in many of his poems for a variety of functions. Key words : semiotics, poetry, Edgar Allan Poe, umberto Eco. الملخص نحاول من خلال بحثنا أن نستعرض أهمية النظرية السميائية في تحليل الشعر خاصة ذلك أن السمة الخاصة التي يتميز بها الشعر تجعله من النوع الأدبي الوحيد الذي يجعل تحليله من التحديات التي تواجه الناقد من أجل الوصول إلى الرأية التي التي بلورها الشاعر في شعره. و لأجل هذا السبب نقترح أنه يجب أن نستثمر في مجال السيمياء في تحليل و دراسة الشعر لأنها توفر لنا آليات و مفاهيم متنوعة التي تسمح بالغور بعمق في تحليل الشعر. و لكن بالرغم من هذا نجد أن الشعر هو الأقل حظا مقارنة مع الانواع الأدبية الأخرى في إستفادته من آليات السيمياء. و على إثر هذا نريد في هذه الدراسة النقدية أن نضيف في هذا المجال و نوضح النتائج المرضيةالتي نتحصل عليها في دراسة الشعر. و على إثر هذا إخترنا مجموعة من الاشعار للشاعر و الكاتب الأمريكي إدغار آلان بو و درسنا فيها الصور المتنوعة لمصطلح " الوحدة" على ضوء مفاهيم و آليات السميائي أمبرتو إيكو. و في الأخير وجدنا أن النتائج جد مرضية و منطقية في تبيان الإستراتيجات الفنية للشاعر في توظيف "الوحدة" من أجل عدة غايات في الكثير من أشعاره و التي سيتم توضيحها من خلال هذه الورقة. الكلمات المفتاحية السيمياء- الشعر- إدغار آلان بو- أمبرتو إيكو
مقال
Keywords: Semiotics ; Poetry ; Edgar Allan Poe ; Umberto Eco; loneliness